2014
DOI: 10.1074/jbc.m114.570978
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Storm Marks Cerebral Metabolism following Brain Trauma

Abstract: Background: In brain metabolism, neurons are fueled by lactate passed to them by glia in a metabolic coupling. Results: Following brain trauma, lactate uptake into neurons from glia was impaired, producing a metabolic lactate storm. Conclusion: Brain trauma results in neuronal-glial metabolic uncoupling, releasing free lactate. Significance: Inhibition of lactate production or its removal may be an important therapeutic strategy for brain trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 58 publications
5
49
0
Order By: Relevance
“…In contrast, our study, suggests that lactate production may significantly increase even in the presence of a satisfactory glucose supply (Table 1) to attend brain metabolic needs. However, as proposed by Lama et al, 201428, the acute increase in the brain tissue lactate concentrations after severe TBI is associated to decreased neuronal uptake, probably leading to irreversible injury and pan‐necrosis. Therefore, although the high extracellular availability of lactate suggests that the metabolic machinery in astrocytes was responsive to the increased energy demands after TBI, neurons were apparently not capable of using lactate as substrate, ultimately contributing to the patient's death.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, our study, suggests that lactate production may significantly increase even in the presence of a satisfactory glucose supply (Table 1) to attend brain metabolic needs. However, as proposed by Lama et al, 201428, the acute increase in the brain tissue lactate concentrations after severe TBI is associated to decreased neuronal uptake, probably leading to irreversible injury and pan‐necrosis. Therefore, although the high extracellular availability of lactate suggests that the metabolic machinery in astrocytes was responsive to the increased energy demands after TBI, neurons were apparently not capable of using lactate as substrate, ultimately contributing to the patient's death.…”
Section: Discussionmentioning
confidence: 92%
“…As previously stated, astrocytes take up glutamate in the synaptic space thereby triggering glycolysis and lactate production, which is shuttled to neurons 15. The flux of these substrates in the body fluids has been explored in the clinical setting as biomarkers of neuroenergetic support, neuron‐to‐astrocyte interactions, and clinical outcomes 28. Recently, Thelin et al, 2014 showed that an increased brain extracellular levels of lactate and pyruvate after TBI were correlated with unfavorable neurological outcome based on Glasgow Outcome Scale29.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while TNF signaling is detrimental to CNS homeostasis, transforming growth factor-β (TGF-β) is strongly neuroprotective as signaling acts to reduce inflammation, excitotoxicity and apoptosis, and to enhance neuronal regeneration [for review, see (31)]. The trend toward increased lactate release in females is also intriguing, as lactate levels are increased during several types of brain injury and are thought to both indicate and enhance tissue damage (63,102). Thus, alcohol-induced astrocyte dysfunction in females is predicted to accelerate alcohol-induced neurotoxicity in a sexually dimorphic fashion.…”
Section: Discussionmentioning
confidence: 98%
“…Augmented glycolysis, such as that occurring in the activated inflammatory cells, leads to increased lactate production that results in intracellular and extracellular acidification. Extracellular lactate is known to have many biological activities (22)(23)(24)(25). However, it is less clear how the export of the intracellular lactate is regulated or what the functional implication of lactate export is during inflammation.…”
Section: Mct4 Is Up-regulated In Lps-treatedmentioning
confidence: 99%
“…For example, augmented aerobic glycolysis was found in LPS-treated dendritic cells and macrophages and has an important role in reg-ulating the activation of these cells (13)(14)(15)(16). Although the biological activities of extracellular lactate are well studied (22)(23)(24)(25), it is less understood how the lactate export is regulated or whether lactate export affects glycolysis during inflammatory activation. In this study, we found that MCT4 is up-regulated in activated macrophages.…”
mentioning
confidence: 99%